2017
DOI: 10.3389/fped.2017.00127
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Problems and Their Underlying Mechanisms in the Esophageal Atresia–Tracheoesophageal Fistula Patient

Abstract: Feeding difficulties such as dysphagia, coughing, choking, or vomiting during meals, slow eating, oral aversion, food refusal, and stressful mealtimes are common in children with repaired esophageal atresia (EA) and the reasons for this are often multifactorial. The aim of this review is to describe the possible underlying mechanisms contributing to feeding difficulties in patients with EA and approaches to management. Underlying mechanisms for these feeding difficulties include esophageal dysphagia, oropharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 81 publications
(115 reference statements)
1
22
1
Order By: Relevance
“…Although survival rates have improved up to 95%, EA is a cause of long-term esophageal and respiratory complications persisting into adulthood (Ijsselstijn, van Beelen, & Wijnen, 2013): dysphagia and gastroesophageal reflux disease (GOR) (Pedersen et al, 2013), feeding difficulties (Menzies, Hughes, Leach, Belessis, & Krishnan, 2017), chronic cough, wheezing, and recurrent airway infections (Porcaro et al, 2017). Respiratory problems and feeding difficulties are frequent during early childhood, whereas problems with swallowing solid and liquid food, choking, coughing and dysphagia are common later (Mahoney & Rosen, 2017). Up to 60% of patients with EA are observed to have associated malformations (Śmigiel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although survival rates have improved up to 95%, EA is a cause of long-term esophageal and respiratory complications persisting into adulthood (Ijsselstijn, van Beelen, & Wijnen, 2013): dysphagia and gastroesophageal reflux disease (GOR) (Pedersen et al, 2013), feeding difficulties (Menzies, Hughes, Leach, Belessis, & Krishnan, 2017), chronic cough, wheezing, and recurrent airway infections (Porcaro et al, 2017). Respiratory problems and feeding difficulties are frequent during early childhood, whereas problems with swallowing solid and liquid food, choking, coughing and dysphagia are common later (Mahoney & Rosen, 2017). Up to 60% of patients with EA are observed to have associated malformations (Śmigiel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Feeding difficulties have been reported in up to 75% of children with OA, including food refusal, lengthy meals, vomiting, choking and food bolus impaction. 6 Despite the high prevalence of feeding difficulties in this population, Puntis et al (1990) showed that only 11% of parents discussed their feeding concerns with medical and nursing staff. 7 Our previous study demonstrated that over 50% of children in the multidisciplinary OA clinic were not eating age-appropriate textures, particularly younger children (P = 0.02).…”
Section: What This Paper Addsmentioning
confidence: 97%
“…A gastrostomy is often placed in the first days of life [1], particularly in cases of long-gap EA. As a result, some patients may miss the chance to acquire a natural swallowing mechanism [6][7][8]. Furthermore, motility problems are quite frequent in children with esophageal atresia [6].…”
Section: Introductionmentioning
confidence: 99%